Nanostructured Biomaterials - Li, Junbai (Advanced Topics in Science and Technology in China, 2010)
Nanostructured materials with designed biofunctions have brought about rapid and significant changes in materials science. "Nanostructured Biomaterials" provides up-to-date reviews of different methods for synthesizing new types of such materials and discusses their cutting-edge technological applications. The reviews mainly focus on potential applications of nanostructured materials in biology and the medical sciences. The book is of general interest to a broad audience of graduate students and researchers active in chemistry, materials science, engineering, biology, and physics. Dr. Junbai Li is a professor at the National Center for Nanoscience and Technology and the Institute of Chemistry, Chinese Academy of Sciences, China.